Modernity at the Margins: Paul Bowles’ Let It Come Down, The Spider’s House, and Moroccan Collaborations. - Moore, Lindsey (Journal of Commonwealth Literature, 2012)
Literary representations of Morocco sometimes challenge specific colonial, national, and nationalist epistemologies. The work of Paul Bowles, in particular, problematizes conventional categories, not only through the extra-national yearnings of protagonists of his fiction, but also due to the hybrid products of collaborations with Moroccan artists. This article grapples with the contested status of an author profoundly engaged with non-Western epistemology and experience, yet susceptible to Orientalist desire. I focus on Bowles’ novels Let It Come Down and The Spider’s House and then on ways in which the author participated in the emergence of a postcolonial Moroccan body of “texts”. Edward Said’s contrapuntal methodology (2004) and the notion of teleological retrospect (Currie 2007) provide an analytical framework, and Said’s emphasis on labyrinthine and occluded literary relations a rationale for analyzing contexts beyond those directly affected by British colonialism. I argue that Bowles increasingly deprivileges expatriate sensibility and anticipates a critical rereading of colonial history; it is also underpinned by an ambivalent view of writing. While his Moroccan corpus repeatedly enacts the difficulty of “telling the other”, it is nevertheless thematically, structurally, and philosophically invested in the challenges of transcoding, translation, and transvaluation. As such, it illuminates interfaces between colonial discourse, late modernist expatriate/travel writing, and early postcolonial production.